Handbook of plant-based fermented food and beverage technology - Arroyo-Lopez, Francisco Noe; Evranuz, E. Ozgul; Hui, Y. H. [ (Yiu H.)] (CRC Press, 2012)
"This second edition of a bestseller examines a wide range of starter cultures and manufacturing procedures for popular plant-based food products. The text focuses on the quality of the final food product, flavor formation and new advances in starter cultures for dairy fermentations using recent examples that depict the main species used, their characteristics, and their impact on the development of other fermented foods. Also new to the second edition: sections on fermented fruit such as apple cider, fermented specialties such as vanilla, and U.S. permitted food ingredients derived each fermented product. "-- Provided by publisher